Parallel evolution of gravity sensing - Romanova, Daria Y.; Moroz, Leonid L. (Frontiers in Cell and Developmental Biology, 2024)
Omnipresent gravity affects all living organisms; it was a vital factor in the past and the current bottleneck for future space exploration. However, little is known about the evolution of gravity sensing and the comparative biology of gravity reception. Here, by tracing the parallel evolution of gravity sensing, we encounter situations when assemblies of homologous modules result in the emergence of non-homologous structures with similar systemic properties. This is a perfect example to study homoplasy at all levels of biological organization. Apart from numerous practical implementations for bioengineering and astrobiology, the diversity of gravity signaling presents unique reference paradigms to understand hierarchical homology transitions to the convergent evolution of integrative systems. Second, by comparing gravisensory systems in major superclades of basal metazoans (ctenophores, sponges, placozoans, cnidarians, and bilaterians), we illuminate parallel evolution and alternative solutions implemented by basal metazoans toward spatial orientation, focusing on gravitational sensitivity and locomotory integrative systems.